Cost Analysis of the Dutch Obstetric System: low-risk nulliparous women preferring home or short-stay hospital birth - a prospective non-randomised controlled study - Nijhuis Jan G; Basten Marloes CM; Evers Silvia MAA; Hendrix Marijke JC; Severens Johan L (BMC, 2009)
Abstract Background In the Netherlands, pregnant women without medical complications can decide where they want to give birth, at home or in a short-stay hospital setting with a midwife. However, a decrease in the home birth rate during the last decennium may have raised the societal costs of giving birth. The objective of this study is to compare the societal costs of home births with those of births in a short-stay hospital setting. Methods This study is a cost analysis based on the findings of a multicenter prospective non-randomised study comparing two groups of nulliparous women with different preferences for where to give birth, at home or in a short-stay hospital setting. Data were collected using cost diaries, questionnaires and birth registration forms. Analysis of the data is divided into a base case analysis and a sensitivity analysis. Results In the group of home births, the total societal costs associated with giving birth at home were €3,695 (per birth), compared with €3,950 per birth in the group for short-stay hospital births. Statistically significant differences between both groups were found regarding the following cost categories 'Cost of contacts with health care professionals during delivery' (€138.38 vs. €87.94, -50 (2.5-97.5 percentile range (PR)-76;-25), p < 0.05), 'cost of maternity care at home' (€1,551.69 vs. €1,240.69, -311 (PR -485; -150), p < 0.05) and 'cost of hospitalisation mother' (€707.77 vs. 959.06, 251 (PR 69;433), p < 0.05). The highest costs are for hospitalisation (41% of all costs). Because there is a relatively high amount of (partly) missing data, a sensitivity analysis was performed, in which all missing data were included in the analysis by means of general mean substitution. In the sensitivity analysis, the total costs associated with home birth are €4,364 per birth, and €4,541 per birth for short-stay hospital births. Conclusion The total costs associated with pregnancy, delivery, and postpartum care are comparable for home birth and short-stay hospital birth. The most important differences in costs between the home birth group and the short-stay hospital birth group are associated with maternity care assistance, hospitalisation, and travelling costs.